Rethinking Engagement: VAK Learning Style Responses to Flipped Classroom Environments - Edelwis Chairunnisa; Andang Saehu; Ahmad Nadhir (Media Publikasi Cendekia Indonesia, 2025)
This study aims to investigate the impact of the flipped classroom method on students' learning engagement, especially visual, auditory and kinesthetic learning styles, considering their learning styles such as visual, auditory, and kinesthetic (VAK). Specifically, it compares students' engagement levels when learning occurs at home versus in the college classroom. Using a mixed-methods design, data were collected from 30 college students (aged 18-24) through a questionnaire consisting of 14 closed-ended and 1 open-ended question. The findings revealed that visual learners showed consistent positive engagement in both settings, with a preference for visual materials that supported their learning. Auditory learners demonstrated higher engagement during in-class sessions with live discussions, while kinesthetic learners exhibited higher engagement during hands-on activities in the classroom. The findings suggest that the flipped classroom model is particularly effective for visual learners, both at home and in the classroom. This research provides implications for educators to design inclusive flipped classroom experiences by incorporating learning media and activities tailored to diverse learning styles, ensuring effective engagement both at home and in the classroom.